(8/9) x (-3/4)➗(1/9) x (-4/5)➗(3/5)

Use the properties of operations and rules for multiplying and dividing to solve it.

7 answers

To solve this expression, we will use the properties of operations and rules for multiplying and dividing.

Let's simplify each multiplication and division separately:

(8/9) x (-3/4) = (-24/36) = -2/3

(1/9) x (-4/5) = (-4/45)

Now, let's simplify the division:

-2/3 ÷ -4/45 = (-2/3) x (45/-4) = (-90/12) = -15/2

Therefore, the value of the expression (8/9) x (-3/4) ÷ (1/9) x (-4/5) ÷ (3/5) is -15/2.
Wrong
Apologies for the mistake. Let's try solving the expression again:

To solve the expression (8/9) x (-3/4) ÷ (1/9) x (-4/5) ÷ (3/5), we first need to simplify the multiplication and division from left to right.

Multiplication: (8/9) x (-3/4) = -24/36 = -2/3

Division: -2/3 ÷ (1/9) = -2/3 x 9/1 = -18/3 = -6

Now, we have -6 x (-4/5) ÷ (3/5)

Multiplication: -6 x (-4/5) = 24/5

Division: 24/5 ÷ (3/5) = 24/5 x 5/3 = 120/15 = 8

Therefore, the value of the expression (8/9) x (-3/4) ÷ (1/9) x (-4/5) ÷ (3/5) is 8.
It has to be a fraction
Apologies for the confusion. Let's solve the expression again:

To solve the expression (8/9) x (-3/4) ÷ (1/9) x (-4/5) ÷ (3/5), we need to simplify the multiplication and division from left to right.

Multiplication: (8/9) x (-3/4) = -24/36 = -2/3

Division: -2/3 ÷ (1/9) = -2/3 x 9/1 = -18/3 = -6

Now, we have -6 x (-4/5) ÷ (3/5) = 24/5 ÷ (3/5)

To divide fractions, we invert the divisor and multiply:

24/5 ÷ (3/5) = 24/5 x (5/3) = (24x5) / (5x3) = 120/15

We can simplify the resulting fraction by dividing the numerator and denominator by their greatest common divisor, which is 15:

120/15 = (120/15) ÷ (15/15) = 8/1

Therefore, the value of the expression (8/9) x (-3/4) ÷ (1/9) x (-4/5) ÷ (3/5) is 8/1.
8 was the right answer
Apologies for the confusion in my previous response. You're right, the simplification of the expression actually results in 8. Thank you for pointing that out.